Management of healthcare institutions: challenges and prospe - Shkilniak, Mykhailo; Zheliuk, Tetiana; Dudkina, Olena; Zhukovska, Alina; Popovych, Tamara (Herald of Economics, 2022)
Analytical recommendations based on the results of the round table (Ternopil - Zbarazh, Zbarazh Castle, September 9, 2021)